AN ANALYSIS FOREIGN LANGUAGE ENGLISH SPEAKING ANXIETY AT SMAN 1 KRAMATWATU - Sintawati, Fairus; Sarkiman, Elsa Dwi; Kirana, Ayu; Tasya, Imelda; Sulhiya, Sulhiya (Faculty of Teacher Training and Education, English Department, UNISKA, Kediri, 2025)
This research aims to define the factors of students’ speaking anxiety and how the students’ strategies to overcome speaking anxiety in the classroom. This research is qualitative descriptive. The subjects in this study were English subject one teacher and four students of 12th grade of SMAN 1 Kramatwatu. The instrument is observation and interview guides. According to Miles & Huberman the analysis consists of three streams of activities that occur simultaneously, namely: data reduction, data presentation, conclusion drawing/verification. The results showed that the factor causing of the students speaking anxiety to speak in the language classroom are: low English proficiency, lack of confidence, lack of familiarity of task, fear of making mistakes, and incomprehensible inputs. There are several strategiest to overcome those anxiety namely preparation, relaxation, positive thinking and support from teacher and classmates.